ON THE ROLE OF THE CENTRAL ASIAN COOPERATION ORGANIZATION WITHIN THE SCO - TOLIPOV, Farkhod (CENTRAL ASIA AND THE CAUCASUS, 2004)
The Shanghai Cooperation Organization (SCO) is over seven years old; it started as the Shanghai Five (Russia, China, Kazakhstan, Kyrgyzstan, and Tajikistan) set up at the Shanghai summit of 26 April 1996, which signed the Treaty on Deepening Military Trust in Border Regions. Since that time summits have developed into a regular feature. The second summit held in Moscow on 24 April, 1997 adopted the Treaty on the Reduction of Military Forces in Border Regions. The third summit held on 3 July 1998 in Almaty concentrated on further strengthening confidence and stability in the region and enhancing trade and economic cooperation. The fourth summit held on 24 August 1999 in Bishkek signed a Joint Declaration on Combating National Separatism, Religious Extremism, and Transborder Crime. The fifth summit was held on 4-5 July 2000 in Dushanbe; it discussed problems of regional security and stability, cooperation in fighting international terrorism and religious extremism, as well as border problems. Attended by President of Uzbekistan Islam Karimov it signed the Dushanbe Declaration and passed a decision on transforming the organization into the Shanghai Forum. The sixth summit held in Shanghai on 15 June 2001 adopted a Declaration on the Establishment of the Shanghai Cooperation Organization and a Convention on Combating Terrorism, Separatism, and Extremism. The seventh summit held on 7 June 2002 in St. Petersburg adopted the SCO Charter, the Agreement on Setting Up the Regional Antiterrorist Organization (RATO), with its center in Bishkek, and the Declaration by the Heads of Member States of the SCO. The eighth summit met in Moscow on 29 May 2003 to make two important decisions: on the SCO Secretariat to be set up in Shanghai and on the transfer of the RATO headquarters from Bishkek to Tashkent.Uzbekistan became the new SCO chairman. The president of the member states endorsed a set of normative documents related to the way the SCO structures (its financial mechanism included) should function. Adopted a financial charter dealing with the procedure for forming and executing the SCO’s budget, as well as setting forth the provisions on the councils of the heads of state, heads of government, foreign ministers, and national coordinators. The Moscow summit also adopted a document on the SCO secretariat, conferences of the ministry and department heads, and permanent representatives of the member states at the Secretariat, as well as on the operating rules for the RATO headquarters.